Polysaccharide hydrogels for multiscale 3D printing of pullulan scaffolds. (5th March 2019) - Della Giustina, Gioia; Gandin, Alessandro; Brigo, Laura; Panciera, Tito; Giulitti, Stefano; Sgarbossa, Paolo; D'Alessandro, Delfo; Trombi, Luisa; Danti, Serena; Brusatin, Giovanna
Abstract: Structurally and mechanically similar to the extracellular matrix (ECM), biomimetic hydrogels offer a number of opportunities in medical applications. However, the generation of synthetic microenvironments that simulate the effects of natural tissue niches on cell growth and differentiation requires new methods to control hydrogel feature resolution, biofunctionalization and mechanical properties. Here we show how these goals can be achieved by using a pullulan-based hydrogel, engineered in composition and server as cell-adhesive hydrogel, 3D photo-printable in dimension, ranging from the macro- to the micro-scale dimensions, and of tunable mechanical properties. For this, we used absorbers that limit light penetration, achieving 3D patterning through stereolithography with feature vertical resolution of 200 μm and with overall dimension up to several millimeters. Furthermore, we report the fabrication of 3D pullulan-modified hydrogels by two-photon lithography, with sub-millimetric dimensions and minimum feature sizes down to some microns. These materials open the possibility to produce multiscale printed scaffolds that here we demonstrate to be inert for cell adhesion, but biologically compatible and easily functionalizable with cell adhesive proteins. Under these conditions, successful cell cultures were established in 2D and 3D. Graphical abstract: Unlabelled Image Highlights: Fabrication of hydrogels scaffolds made of methacrylathed pullulan. Multiscale light assisted 3D printing (visible stereolithography and two-photon lithography). Functionalization of pullulan based scaffolds with extracellular matrix proteins Demonstration that, after functionalization, the scaffolds support adhesion and growth of ephitelial and mesenchymal cells